2019
DOI: 10.3389/fevo.2019.00327
|View full text |Cite
|
Sign up to set email alerts
|

Automated VHF Radiotelemetry Revealed Site-Specific Differences in Fall Migration Strategies of Semipalmated Sandpipers on Stopover in the Gulf of Maine

Abstract: to a greater understanding of stopover behavior and the degree of connectivity among stopover sites, which should be taken into account for conserving migratory bird habitat across broad spatial scales.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
(62 reference statements)
2
4
0
Order By: Relevance
“…Almost all birds detected leaving the region crossed mainland Nova Scotia and departed over the ocean, not appearing on receivers on the coast of the United States. This confirms the migration path proposed by previous radar, observational studies and computer simulation (Williams et al, 1977;Richardson, 1979;Lank, 1983) and is consistent with the observations of Holberton et al (2019) for Semipalmated Sandpipers departing the northern Gulf of Maine. Thus it appears they have a consistent departure strategy.…”
Section: Conditions Affecting Departure Timingsupporting
confidence: 92%
See 1 more Smart Citation
“…Almost all birds detected leaving the region crossed mainland Nova Scotia and departed over the ocean, not appearing on receivers on the coast of the United States. This confirms the migration path proposed by previous radar, observational studies and computer simulation (Williams et al, 1977;Richardson, 1979;Lank, 1983) and is consistent with the observations of Holberton et al (2019) for Semipalmated Sandpipers departing the northern Gulf of Maine. Thus it appears they have a consistent departure strategy.…”
Section: Conditions Affecting Departure Timingsupporting
confidence: 92%
“…Further, birds radiotagged on Coats Island, NU, Canada and in James Bay, ON, Canada between 2014 and 2018 were detected for 7-27 days in the Bay of Fundy (n = 10, Friis, Smith, Neima, Paquet and Hamilton, unpublished data). Finally, our minimum length of stay estimates are closer to estimates from the Gulf of Maine, a nearby staging area for SESA where the estimated staging period was found to be 9-15 days (Holberton et al, 2019).…”
Section: Discussionsupporting
confidence: 71%
“…In addition to fuelling, it is widely believed that stopovers serve as periods during which migrants rest and/or recover from the preceding migratory endurance flight (e.g. Biebach, Friedrich & Heine, 1986; Latta & Brown, 1999; Dunn, 2000; Salewski & Schaub, 2007; Taylor et al ., 2011; Schofield et al ., 2018b; Holberton et al ., 2019; DeSimone et al ., 2020). That an organism needs to rest and recover physiologically after a period of endurance exercise seems a plausible explanation for stopping over.…”
Section: The Multiple Functions Of Stopovermentioning
confidence: 99%
“…Our results are consistent with Sprague et al (2008), who found no movement of individuals between Chignecto Bay and the Minas Basin (although Cobequid Bay was not included in that study and the tracking conducted was much more limited). Further, Holberton et al (2019) found the Semipalmated Sandpipers tagged and tracked in eastern Maine, contiguous with the outer Bay of Fundy, also used a restricted set of local sites and did not transfer to more southern areas, which were used by a different population of birds. Studies of intra-annual regional fidelity in shorebirds during migration are limited, though a similar result was also noted in Red Knots (Calidris canutus roselaari) during spring migration on the Pacific coast (Buchanan et al 2012).…”
Section: Intra-and Interannual Regional Fidelitymentioning
confidence: 99%